Microbial succession and interaction in vacuum-packed beef: a longitudinal study of bacterial and fungal dynamics - Franz-Ferdinand Roch; Monika Dzieciol; Cameron R. Strachan; Muhammad Sharjeel Chaughtai; Narciso M. Quijada; Tea Movsesijan; Evelyne Selberherr (npj Science of Food)
Abstract The microbial dynamics of vacuum-packed (VP) beef are shaped by interactions between bacterial and fungal communities, influencing spoilage and meat quality during storage. While bacterial succession is well studied, fungal roles remain underexplored. We examined microbial communities in VP beef over 85 days using spike-in, qPCR, 16S/18S rRNA gene amplicon sequencing, culture-based methods, whole genome sequencing, and co-culture experiments. Initially dominated by Pseudomonas and Brochothrix, the bacterial community shifted toward lactic acid bacteria (LAB) by day 15. Fungal communities remained diverse, with Kurtzmaniella, Barnettozyma, Debaryomyces, and Yarrowia as key genera. Co-culture experiments revealed a triangular interaction: yeasts enhanced LAB, LAB inhibited Enterobacterales, and Enterobacterales suppressed yeasts. Genomic analyses suggest yeast metabolites support LAB, LAB inhibit via acids and bacteriocins, and Enterobacterales produce fungal cell wall-degrading enzymes. These findings highlight fungi’s overlooked role and the importance of inter-kingdom interactions in meat microbiomes, offering a foundation for strategies to improve meat safety and shelf life.